Lymphotoxin alpha eradicates acute myeloid leukemia and simultaneously promotes healthy hematopoiesis in mice - Höckendorf, Ulrike; Dutta, Sayantanee; Kloos, Arnold; Runtsch, Marah; Zötsch, Carina; Vosberg, Sebastian; Wang, Yongjie; Kienreich, Sophie; Flasch, Bettina; Malovan, Grazia; Jäger, Vanessa; Stanzer, Stefanie; et al. (Science translational medicine, 2025)
Acute myeloid leukemia (AML) is characterized by frequent relapse, which is driven by resistant leukemic stem or progenitor cells (LSCs). Here, we reported on a tumor-suppressive mechanism that can be harnessed to simultaneously clear LSCs and promote healthy hematopoiesis. Genetic deletion of the tumor necrosis factor (TNF) superfamily member lymphotoxin alpha (Lta) blocked cell death and accelerated leukemogenesis in murine AML models. Accordingly, exposure of leukemic cells to exogenous recombinant lymphotoxin alpha (LTα3) induced myeloid differentiation and, in part, cell death in AML progenitors. In syngeneic and patient-derived xenograft mouse models, exposure to recombinant LTα3 resulted in deep and durable remissions. LTα3 repressed leukemia by depleting tumor necrosis factor receptor (TNFR)-associated factor 2 (TRAF2) through activation of TNF receptors TNFR1 and TNFR2. In contrast with conventional therapies, LTα3 exerted only minimal toxicity on the healthy hematopoiesis but instead promoted hematopoietic progenitors. Leveraging this endogenous tumor-suppressive mechanism may decouple treatment efficacy on malignant cells from undesired bone marrow suppression.
Veröffentlicht: 26. November 2025
Gesehen am 30.01.2026